CART: a chemical annotation retrieval toolkit - Deghou, Samy Lyes; Zeller, Georg; Iskar, Murat; Driessen, Marja; Castillo, Mercedes; van Noort, Vera; Bork, Peer (Bioinformatics, 2016)
Abstract. Motivation: Data on bioactivities of drug-like chemicals are rapidly accumulating in public repositories, creating new opportunities for research in
Gesehen am 07.05.2020